Analisis Kinerja Keuangan Pada Rumah Sakit Umum Daerah (RSUD) Dr. Zainal Umar Sidiki Kabupaten Gorontalo Utara - Fonie Tambuwun; Idrus Usu; Ilyas Lamuda; Julie Abdullah (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to analyze the financial performance of the Regional General Hospital (RSUD) dr. Zainal Umar Sidiki, North Gorontalo Regency. This study uses quantitative methods with data analysis techniques used is financial ratio analysis. The results of the study using the cash ratio approach, current ratio, debt collection period ratio, fixed asset turnover ratio, return on assets, return on equity, inventory turnover ratio, and POBO ratio, it is obtained that the financial performance of RSUD dr. Zainal Umar Sidiki, North Gorontalo Regency, for the last three years has experienced fluctuations and it can be said that it is not yet in the good category based on standards